Cardiac remodeling in preterm infants with prolonged exposure to a patent ductus arteriosus. (22nd February 2017) - de Waal, Koert; Phad, Nilkant; Collins, Nick; Boyle, Andrew
Abstract: Background: Sustained volume load due to a patent ductus arteriosus (PDA) leads to cardiac remodeling. Remodeling changes can become pathological and are associated with cardiovascular disease progression. Data on remodeling changes in preterm infants is not available. Methods: Clinical and echocardiography data were collected in preterm infants <30 weeks gestation on postnatal day 3 and then every 7–14 days until closure of the ductus arteriosus. Images were analyzed using conventional techniques and speckle tracking. Remodeling changes of infants with prolonged (>14 days) exposure to a PDA were compared to control infants without a PDA. Results: Thirty out of 189 infants had prolonged exposure to a PDA. The left heart remodeled to a larger and more spherical shape and thus significantly increased in volume. Most changes occurred in the first 4 weeks, plateaued, and then returned to control values. Systolic function and estimates of filling pressure increased and effective arterial elastance reduced with a PDA, however contractility was unchanged. Wall thickness increased after 4 weeks of increased volume exposure. Conclusion: The preterm PDA induces early and significant remodeling of the left heart. A compensated cardiac physiology was seen with preserved systolic function, suggesting adaptive rather than pathological remodeling changes with prolonged exposure to a PDA.